1999
DOI: 10.1085/jgp.113.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Local Control Models of Cardiac Excitation–Contraction Coupling

Abstract: In cardiac muscle, release of activator calcium from the sarcoplasmic reticulum occurs by calcium- induced calcium release through ryanodine receptors (RyRs), which are clustered in a dense, regular, two-dimensional lattice array at the diad junction. We simulated numerically the stochastic dynamics of RyRs and L-type sarcolemmal calcium channels interacting via calcium nano-domains in the junctional cleft. Four putative RyR gating schemes based on single-channel measurements in lipid bilayers all failed to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
120
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(122 citation statements)
references
References 46 publications
1
120
1
Order By: Relevance
“…The inhibitory feedback overriding the regenerative CICR may represent the long-sought mechanism for the termination and stability of intracellular Ca 2ϩ release. We have previously shown that a model RyRC array based on in vitro RyRC properties and local CICR fails to reproduce proper termination of Ca 2ϩ sparks and cannot account for the microscopic stability of intracellular Ca 2ϩ release (24,25). In light of the present finding, we incorporated an inhibitory coupling by introducing a strong Ca 2ϩ -dependent inactivation of RyRCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory feedback overriding the regenerative CICR may represent the long-sought mechanism for the termination and stability of intracellular Ca 2ϩ release. We have previously shown that a model RyRC array based on in vitro RyRC properties and local CICR fails to reproduce proper termination of Ca 2ϩ sparks and cannot account for the microscopic stability of intracellular Ca 2ϩ release (24,25). In light of the present finding, we incorporated an inhibitory coupling by introducing a strong Ca 2ϩ -dependent inactivation of RyRCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro properties of RyRCs, the classic Ca 2ϩ -induced Ca 2ϩ release (CICR) mechanism (23) would predict an all-or-none activation of the RyRC array and an everlasting local Ca 2ϩ release, which cannot explain the prompt termination of Ca 2ϩ sparks and the microstability of intracellular signaling (24,25). The relatively constant Ca 2ϩ spark rise time (Ϸ10 ms in the heart) indicates a stereotypical open time of RyRCs (25) whereas RyRCs in vitro always follow exponential open-time distributions (5,17,20).…”
mentioning
confidence: 99%
“…Therefore, even though the involvement of multiple channels is strongly supported here, their structural location remains to be established. Because Ca 2ϩ release during sparks starts and ends abruptly (23), an allosterically connected cluster (17,44) may be at work. These and other issues must be clarified to base a cellwide picture of Ca 2ϩ release on the properties of its channels and their sensors.…”
Section: Discussionmentioning
confidence: 99%
“…They may be functionally distinct from those created by long-term pathology. Because tight coupling between most RyR clusters and LCCs is essential to maintain local control of CICR (48,49) TT Imaging and Analysis. Myocytes were loaded with the lipophilic membrane marker Di-8-ANEPPS (10 M in Tyrode solution for 10 min).…”
Section: Tt Remodeling Of Fetal Phenotype: a Unique Finding From Shr mentioning
confidence: 99%